2011
DOI: 10.1103/physreve.84.051507
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and crystallization phenomenon of supercooled and glassy DNA and RNA nucleosides:β-adenosine,β-thymidine, andβ-uridine

Abstract: Nucleosides are chemical compounds that have an extremely important biological role; they can be found in all types of living organisms. They are crucial components from which DNA and RNA acids are built. In addition, nucleosides are key regulators of many physiological processes. In this paper, the molecular dynamics in the liquid and glassy state of three selected nucleosides, β-adenosine, β-thymidine, and β-uridine, was investigated by means of dielectric spectroscopy. Our results revealed multiple relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…It can be seen that the relaxation strength of the α process scales as 1/ T , as expected from the Kirkwood–Fröhlich equation . The secondary relaxation is a simply activated process, following the Arrhenius law with activation energy E a = 38.0 ± 0.6 kJ/mol, a relatively low value that is close to that reported in ref and which suggests an intramolecular origin of this relaxation process, as also discussed below. Instead, the temperature dependence of the α relaxation time could be modeled with a Vogel–Fulcher–Tamman (VFT) function, defined by where τ ∞ is the high temperature limit of the relaxation time, D is the so-called strength parameter (proportional to the inverse of the fragility index, see below), and T 0 is the Vogel–Fulcher temperature, whose value indicates the departure from a simply activated behavior.…”
Section: Results and Discussionsupporting
confidence: 84%
“…It can be seen that the relaxation strength of the α process scales as 1/ T , as expected from the Kirkwood–Fröhlich equation . The secondary relaxation is a simply activated process, following the Arrhenius law with activation energy E a = 38.0 ± 0.6 kJ/mol, a relatively low value that is close to that reported in ref and which suggests an intramolecular origin of this relaxation process, as also discussed below. Instead, the temperature dependence of the α relaxation time could be modeled with a Vogel–Fulcher–Tamman (VFT) function, defined by where τ ∞ is the high temperature limit of the relaxation time, D is the so-called strength parameter (proportional to the inverse of the fragility index, see below), and T 0 is the Vogel–Fulcher temperature, whose value indicates the departure from a simply activated behavior.…”
Section: Results and Discussionsupporting
confidence: 84%
“…4(b). 19,22,23,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] It was noted before that the aforementioned relation of activation energy to T g is not universal. 41 Many true JG β-relaxations, not shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relationships between α-relaxation and JG β-relaxation times had been established by the CM 7,9,10,58 and are consistent with the results from considerable number of experimental studies in many glass-forming systems. 7,[9][10][11][12]14,15,17,[19][20][21][22][23]27,28,[30][31][32][33]39,40,44,47,48,53,56,57 One relation showed that the dynamic separation between the αand the JG β-relaxations depends on the coupling parameter n (n ≡ (1 − β KWW )), and it is given by…”
Section: Methodsmentioning
confidence: 99%
“…Usually, secondary relaxation processes originating from the local motions of the entire molecule (i.e., JG processes) have a significantly greater energy barrier. For example, the E a of the intermolecular (JG) secondary relaxation of β-adenosine, β-uridine, celecoxib, and telmisartan are equal to 80, 77, 80, and 82 kJ/mol, respectively …”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, the E a of the intermolecular (JG) secondary relaxation of β-adenosine, β-uridine, celecoxib, and telmisartan are equal to 80, 77, 80, and 82 kJ/mol, respectively. 39 In order to parametrize the temperature dependence of the CLP's structural (α) relaxation time revealing a non-Arrhenius behavior (see squares on Figure 5), we employed the Vogel− Fulcher−Tammann (VFT) equation 40−42…”
Section: Molecular Pharmaceuticsmentioning
confidence: 89%